2020
DOI: 10.1111/bdi.12993
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and neuroimaging correlates of cardiorespiratory fitness in adolescents with bipolar disorder

Abstract: Introduction: Cardiovascular disease (CVD) is exceedingly prevalent, and occurs prematurely in individuals with bipolar disorder (BD). Cardiorespiratory fitness (CRF), arguably the most important modifiable CVD risk factor, is also associated with brain structure and function. There is a gap in knowledge regarding CRF in BD, particularly in relation to brain structure.Methods: Adolescents with BD (n = 54) and healthy controls (HC; n = 53) completed semi-structured diagnostic interviews, self-report questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
0
3
0
Order By: Relevance
“…Gender plays a critical role in the diagnosis and severity of the bipolar disorder in addition to the effect of age on brain function in bipolar disorder patients. For example, one study found a significant decline in heart and lung health in adolescents with bipolar disorder, particularly females [10]. The structure and function of cortical and subcortical regions associated with bipolar disorder are consistently affected by sex differences [11].…”
Section: Introductionmentioning
confidence: 99%
“…Gender plays a critical role in the diagnosis and severity of the bipolar disorder in addition to the effect of age on brain function in bipolar disorder patients. For example, one study found a significant decline in heart and lung health in adolescents with bipolar disorder, particularly females [10]. The structure and function of cortical and subcortical regions associated with bipolar disorder are consistently affected by sex differences [11].…”
Section: Introductionmentioning
confidence: 99%
“…In recent studies with adolescents with BD a link between cardiorespiratory fitness and depressive symptoms was identified (Popel et al 2021 ). Intriguingly, behavior change counselling was shown to be effective in encouraging adolescents with BD to engage in more aerobic training (Khoubaeva et al 2023 ), but there is a scarcity of research trials on adults with BD and exercise training.…”
Section: Introductionmentioning
confidence: 99%
“…A recent cross‐sectional study by Popel et al 2 analyzed the relationship between cardiorespiratory fitness (CRF), brain structure, and symptomatology in 54 adolescents with BD compared with 53 healthy controls. They used power (W/kg) in a 20‐min bicycle exercise at 60–80% of the estimated maximum heart rate as a proxy of CRF.…”
mentioning
confidence: 99%